The Interpenetration between Amaterasu Oomikami and the Japanese Environment - Lawanda, Ike Iswary (Makara Human Behavior Studies in Asia, 2008)
The article indicate the interpenetration between Amaterasu Oomikami and environment within the Japanese thought. The protection of environment as a product of interpretation of Japanese culture in reciprocal relation is categorized by: the normative – the real; the sacred – the profane; supranatural world – human world. The system classification is the product of knowledge from the Japanese way in seeing the world based on the classification of the inside (uchi) – the outside (soto/yoso). This classification and its attributes produce differentiation between the inside – the outside. The environment destruction is considered as disgrafuk and dirty action. Any violation should be given sanctions. The Japanese watch over their environment by following the pattern of jinja and tera maintainance.. The purity of human behaviour is to protect the environment whilst dirty actions should be avoided. The Japanese view the environment in relevant to the religious belief as primordial as Amaterasu Oomikami the great ancestor of Japanese tenno. The belief in the sacred enfolds the life of the Japanese to nurture collective consciousness in every individual and groups in local, prefecture and nation-state hierarchically. Collective consciousness or solidarity in individuals is socialized by and within institutions in order to produce confirmity among individuals and with the environment. Interpretive method with symbolic approach produce the understanding of Amaterasu Oomikami and the environment as a system of relations in Japanese interpenetrated in the culture through a set of values and actions.